QuantiFERON-TB Gold In-Tube test (QFT-GIT) for the screening of latent tuberculosis in recent immigrants to Italy - Saracino, Annalisa; Scotto, Gaetano; Fornabaio, Chiara; Martinelli, Domenico; Faleo, Giuseppina; Cibelli, Donatella; Tartaglia, Alessandra; Di Tullio, Rocco; Fazio, Vincenzina; Prato, Rosa; Monno, Laura; Angarano, Gioacchino (The New microbiologica, 2009)
To evaluate the agreement between QuantiFERON-TB Gold In-Tube test (QFT-GIT) and tuberculin skin test (TST) for the screening of latent tuberculosis infection (LTBI) in recent immigrants to Italy, 279 subjects were submitted to concomitant TST and QFT-GIT. The agreement was analyzed using k statistics. A total of 72/279 (25.8%) individuals were TST positive, while 107/279 (38.3%) were QFT-GIT positive. The overall agreement between QFT-GIT and TST was 70.9%, with k statistic of 0.35. Using different TST and QFT-GIT cut-offs, the best concordance value was obtained for QFT-GIT at > 2.64 IU/ml and TST at > 10mm (k = 0.409). Discordant results were found for 58 subjects (21%) with QFT-GIT positive/TST negative and 23 (8%) with QFT-GIT negative/TST positive. A high amount of discordance QFT-GIT+/TST- was described. QFT-GIT might increase the identification of LTBI cases among recent immigrants.